ETHICS OF POLITICAL ENTREPRENEURSHIP DURING THE COVID-19 OUTBREAK IN RURAL INDONESIAN VILLAGES - Sobari, Wawan (Universitas Padjadjaran, 2025)
This study explores the political entrepreneurship ethics of village heads in setting village development policies and the context of the COVID-19 pandemic. This study applies a qualitative methodology and observational analysis method with the interview as the main data-gathering technique, discovering musyawarah (deliberation), obedience to regulation, transparency and participation, empathy, priority scale, and Islamic teachings as the principles held by village heads in policy-making. The village heads also draw on musyawarah, obey regulations, and transparency and inclusiveness to avoid conflicts of interest in making policies. Meanwhile, the justification for policy-making is based on regulation and musyawarah. The results of the analysis demonstrate the convergence of political entrepreneurship ethics, namely, adherence to rules and musyawarah, in setting village development policies. They are inseparable from the context of the COVID-19 pandemic. The findings of exploring principles, efforts, and ethical justification of policy-making help to understand the political entrepreneurial actions, which have been left unexplained in the analytical framework of political entrepreneurship as an independent variable. Finally, the context of the pandemic needs to be understood in relation to changes in the policy process. The outbreak can amend the ethical meaning of obeying regulations and musyawarah in setting the village development policies that are implemented by political entrepreneurs. This implies that a pandemic can be considered for its contribution to shaping the ethics of political entrepreneurship.